Bilingualism in Colombia Higher Education - Martínez Rincón, Sandra Liliana (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This theme review describes aspects related to bilingualism and its incidence in higher education. Specifically, the author shows a brief overview of what bilingualism means; what the National Bilingual Program started in 2004 and its evolution into Colombia, very well for 2015 entail in terms of their impact on both teaching and learning; and the importance for the Ministry to modify certain aspects regarding bilingualism in education in our country.The paper also includes some studies and theories which support the author’s statements as well as the introduction of some current events at a private university in Sogamoso, Colombia, which are directly related to the matter of bilingualism. Finally, the author presents some conclusions from the present paper.